Analisis Wacana Kritis Pemberitaan Hukum di Media Online: Kajian Teori Norman Fairclough - Sihombing, Rosi Anita; Nainggolan, Santa Elfira; Farasi, Tessa Anastasia; Jesica, Verenanda; Affandi, Yaszmin Putri; Ritonga, Mara Untung; Arianto, Tomi (Indo-MathEdu Intellectuals Journal, 2026)
The role of online media in shaping public perceptions of legal justice through language construction. The research problem focuses on how perpetrators of petty crimes, corruption, and narcotics are represented in the news, how discursive practices influence the construction of meaning, and how the discourse reflects power relations. The study aims to analyze the representation of criminal perpetrators and uncover the ideology at work in legal reporting in Indonesian online media, namely Kompas.com and Detik.com, through a Critical Discourse Analysis approach using Norman Fairclough's three-dimensional model. The method used is descriptive qualitative research with data collection using listening and note-taking techniques. The results show differences in representation based on social class and type of crime. Media language tends to reproduce legal-formalistic ideology and shows symbolic inequality in the construction of justice. The conclusion of this study shows that the media not only conveys facts but also shapes certain social realities that reproduce power relations and class inequality in the Indonesian legal system.